КОНФЛИКТ «ЛИЧНОСТЬ И РЕАЛЬНОСТЬ» В РОМАНЕ Ж.-Ф. ТУССЕНА «МЕСЬЕ» (World Science, 2019)
The article is dedicated to the work of Toussin, author of the novel "Monsieur". The novel, written in the style of "minimalism", lacks a logical, consistent narrative. At the same time, scrupulous detailing of all his actions, actions, and conditions prevails. The episodes described in detail are not further developed. Direct allusions of educational literature in the work of Toussin are absent. Toussin’s novel "Monsieur", most likely, is a peculiar variation of the game with the philosophical story of the XVIII century, where there is a hidden dialogue between the author and Voltaire.